1,3-Oxazinan-2-ones from Amines and 1,3-Diols through Dialkyl Carbonate Chemistry - McElroy, Con Robert; Aricò, Fabio; Tundo, Pietro (Synlett, 2012)
A one-pot green synthesis of 1,3-oxazinan-2-ones from amines and 1,3-diols in the presence of a dialkyl carbonate and potassium tert-butoxide is described. Four dialkyl carbonates were utilised: dimethyl carbonate, diethyl carbonate, diprop-2-yl carbonate, and tert-butyl methyl carbonate. The more hindered the dialkyl carbonate used, the higher the yield of 1,3-oxazinan-2-one. Four 1,3-diols were reacted having primary–primary, primary–secondary, primary–tertiary, and secondary–tertiary functionalities, with the yield of oxazinanone decreasing with increasing hindrance of the diol. In the case of the diols containing primary and either secondary or tertiary functionality, the substituent(s) were selectively found in the 6-position of the so-formed oxazinanone. The optimized conditions were then employed with different nucleophiles, namely phenylhydrazine, aniline, and n-octylamine.
Keywords: green chemistry; cyclisation; heterocycles; diols; dialkyl carbonates